Gastrointestinal toxicity during induction treatment for childhood acute lymphoblastic leukemia: The impact of the gut microbiota. Issue 7 (16th March 2020) - De Pietri, Silvia; Ingham, Anna C.; Frandsen, Thomas L.; Rathe, Mathias; Krych, Lukasz; Castro‐Mejía, Josue L.; Nielsen, Dennis S.; Nersting, Jacob; Wehner, Peder S.; Schmiegelow, Kjeld; Hasle, Henrik; Pamp, Sünje J.; et al.
Abstract : Intestinal mucositis is a common side effect of chemotherapy leading to diarrhea, abdominal pain and increased risk of infections. The intestinal microbiota has been recognized as a key regulator of mucosal immune responses. Therefore, we hypothesized that intestinal microbial changes would be associated with enterocyte loss and systemic inflammation during induction treatment for childhood acute lymphoblastic leukemia (ALL). We prospectively included 51 children newly‐diagnosed with ALL treated in Denmark in 2015–2018. Plasma C‐reactive protein (CRP), plasma citrulline (marker of functional enterocytes mass) measurements and fecal samplings were performed on treatment Days 1, 8, 15, 22 and 29. Moreover, intestinal mucositis was scored by a trained nurse/physician. Fecal samples in patients and 19 healthy siblings were analyzed by 16S rRNA gene sequencing (V3–V4 region). Bacterial alpha diversity was lower in patients compared to siblings. It decreased from Day 1 to Days 8–22 and increased on Day 29. Shannon alpha diversity index was correlated with CRP on Days 15–29 (rho = −0.33−0.49; p  < 0.05) and with citrulline on Days 15 and 29 (although with p values <0.06, rho = 0.32–0.34). The abundance of unclassified Enterococcus species (spp.) was correlated with CRP on Days 22–29 (rho = 0.42–0.49; p  < 0.009), while the abundance of unclassified Lachnospiraceae spp. was correlated with citrulline on days 8–15 (rho = 0.48–0.62, p  < 0.001). Systemic inflammation, enterocyte loss and relative abundance of unclassified Enterococcus spp. reached a peak around Day 15. In conclusion, specific changes in the microbiota were associated with the severity of enterocyte loss and systemic inflammation during chemotherapy. Abstract : What's new? Intestinal mucositis, and the associated abdominal pain, diarrhea, and infections, frequently plague patients who receive chemotherapy. The microbes that inhabit the gut help regulate mucosal immune responses. These authors investigated how the gut microbiota changes during chemotherapy for childhood acute lymphoblastic leukemia (ALL). They tested the patients weekly and found a sharp drop in microbiota diversity after starting chemotherapy, as well as an overgrowth of enterococci species. The authors suggest that maintaining a high microbial diversity in the gut may help reduce the toxicity associated with intestinal mucositis.